A scoping review of research methodologies used on studies of gender and sexuality within mathematics education - Ana Dias; Weverton Ataide Pinheiro (Perspectivas da Educação Matemática, 2024)
We conducted a review of empirical research published in academic journals that had studied gender and sexuality in mathematics education, with regards to the methodologies they used. Articles published between 2020 and 2024 and in the English, Portuguese, Spanish or French languages were searched in large databases, using a systematic approach. Rather than synthesizing the results of the studies, this review aimed focused on the methodologies used. Of the twenty-three studies raised by the search, four used quantitative methodologies. Methods used in quantitative studies included: discourse analysis, content analysis, interviews with drawings, analysis of interactions in videos, task analysis, interventional studies, interviews followed by data coding, focus groups, life stories, cross-case analysis, document analysis, longitudinal mixed methods and comparative methodologies. We paid particular attention to the movement of the field towards a discursive notion of gender and sexuality and the methodological challenges brought by this and other aspects of post-structural theorizations.